2005
DOI: 10.1002/jrs.1428
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Raman spectroscopy in white portland cement hydration: long‐term study at room temperature

Abstract: The long-term hydration of white portland cement has been followed through micro-Raman spectroscopy, choosing for excitation the most adequate laser wavelength as deduced from a critical analysis of the previously reported Raman data. The bands of the corresponding spectra were attributed to the various anhydrous and hydrated phases, with full hydration of the anhydrous phases taking place after 180 days. Sulphoaluminates were seen to form in two different local environments, at 3 and 180 days respectively. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 12 publications
0
49
0
1
Order By: Relevance
“…However, Schneider et al [22] attributed this same peak to the presence of C 3 AH 6 in cement pastes containing activated slag. Martínez-Ramírez et al [17], analyzing white cement hydration with Raman spectroscopy, observed the formation of sulphate-containing phases that they were unable to identify. Klimesch and Ray…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Schneider et al [22] attributed this same peak to the presence of C 3 AH 6 in cement pastes containing activated slag. Martínez-Ramírez et al [17], analyzing white cement hydration with Raman spectroscopy, observed the formation of sulphate-containing phases that they were unable to identify. Klimesch and Ray…”
Section: Results and Discusionmentioning
confidence: 99%
“…In a previous paper, Martínez-Ramírez et al [17] described a comprehensive micro-Raman study on white cement hydration cured at 20 ºC for 360 days.…”
Section: Introductionmentioning
confidence: 99%
“…The trend of the doublet centered near 860 cm −1 confirmed that alite hydrated more rapidly than belite, according to the literature. [20,24,25] With regard to the spectra recorded on the upper surface of the cements (Fig. 2(A); spectra b and d), it is interesting to note that only the surface of the wTC-TCP sample showed a band at 965 cm −1 , attributable to the ν 1 PO 4 3− mode of apatites.…”
Section: Ageing In Dpbsmentioning
confidence: 99%
“…2(A); spectra b and d), a prominent ν 1 CO 3 2− band was observed at 1088 cm −1 , with a shoulder at about 1075 cm −1 ; this spectral profile (FWHM of 14 cm −1 ) indicated the presence of carbonate ions in different local environments, as previously observed by other authors. [24] The band at 1088 cm −1 can be attributed to calcite and/or aragonite, whereas a component at about 1075 cm −1 has been reported for vaterite. [22] In the spectra recorded in the inner fractured sides (Fig.…”
Section: Ageing In Dpbsmentioning
confidence: 99%
“…However some studies report the use of Raman spectroscopy to investigate cementitious hydrates: namely to distinguish thaumasite Ca 6 Si 2 (OH) 12 ·(CO 3 ) 2 ·(SO 4 ) 2 ·24H 2 O from ettringite Ca 6 Al 2 (OH) 12 ·(SO 4 ) 3 ·26H 2 O, (Brough and Atkinson, 2001-Jallad et al, 2001-Sahu et al, 2002 and to characterize the C-S-H, calcium silicate hydrate, phase (Kirkpatrick et al, 1997). The last two years there has been an increasing interest in applying Raman analyses on wet hydrating samples as mentioned by Skibsted and Hall (2007) and indicating by the numerous recent literature: hydration/carbonation of aluminate phases (Black et al, 2006a and2006b), silicate phases (Ibanez et al, 2007), portlandite (El-Turki et al, 2007) and cement (Martinez-Ramirez et al, 2006-Gastaldi et al, 2007, structural features of C-S-H , corrosion (Poupard et al, 2006) and sulfate-attack (Ma et al, 2006) of concrete. The aim of our study was to use the well known sulfated hydrated cementitious materials (ettringite and monosulfoaluminate Ca 4 Al 2 (OH) 12 ·SO 4 ·6H 2 O) to explore the possibilities given by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%